Предмет: Математика,
автор: kalimtaevarman
(X-y=2
(2x-3y=-1
{X=y+2
{2(y+2)-3y=-1
Ответы
Автор ответа:
12
1. (x-y=2 |-2
(2x- 3y=-1 |1
(-2x +2y=-4
(2x -3y = -1
(2y=-4
(-3y=-1
(y=-2
(y=-3
(2x- 3y=-1 |1
(-2x +2y=-4
(2x -3y = -1
(2y=-4
(-3y=-1
(y=-2
(y=-3
Автор ответа:
2
{X=y+2
{2(y+2)-3y=-1
2y+4-3y=-1
-y=-5
y=5
{2(y+2)-3y=-1
2y+4-3y=-1
-y=-5
y=5
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: История,
автор: bAlOdYa
Предмет: Алгебра,
автор: Анастасия080201
Предмет: Математика,
автор: яма2